Do Chinese residential colleges narrow the education disparity caused by socioeconomic status? a comparison of public and private universities using two main approaches to assess disparities in access and academic attainment - Gui, Pingping; Alam, Gazi Mahabubul (Multidisciplinary Digital Publishing Institute, 2024)
Education is acknowledged as vital for a nation’s economic progress, yet socioeconomic status often dictates access to high quality education, endangering the achievement of the United Nations’ Sustainable Development Goal 4 (SDG 4), where equitable learning is paramount. Previous studies suggest that public residential colleges (RCs) can narrow the gap in achievement among students of varying socioeconomic status (SES). Nonetheless, they do not guarantee participants equal opportunity across all SES levels to attend RCs. Their effectiveness in private higher education institutions, particularly in China, remains underexplored. This study compares RCs in the public and private sectors to examine their role in promoting sustainable education in China. Employing the proportional stratified sampling technique, questionnaires were distributed among 615 RC students from both the public and private sectors. Through descriptive and multiple regression analyses, findings strongly indicate that RCs—whether in public or private universities—cannot guarantee equal access to RCs for learners from various SESs. Particularly, the enrolment disparity in the private sector is more pronounced. Despite these differences, RCs, regardless of institutional affiliation, contribute to narrowing academic discrepancies, as measured by Cumulative Grade Point Average (CGPA), among students from various SES backgrounds. This underscores the significance of RCs in reducing academic attainment disparities across different types of colleges. Consequently, while RCs prove to be effective in narrowing academic discrepancies, there is a pressing need to prioritize equal access to RCs for individuals from disadvantaged SES backgrounds. Addressing this challenge is crucial for tackling issues linked to sustainable education, and in this way, ensure the SDGs are actually achieved. © 2024 by the authors.